PENGELOLAAN SAMPAH RUMAH TANGGA (STUDI PENELITIAN DI DESA KARANG INTAN KECAMATAN KARANG INTAN KABUPATEN BANJAR) - Jumarianta Jumarianta (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
This research intends to find, understand and explain the problems as the phenomenon that occurs. Data collecting researchers do by using more and collect information by deepening the phenomenon studied.Then make an analysis by connecting the existing facts and the data that the researchers get in the field in accordance with the results of observation. After the data obtained from the field then the data isprocessed and analyzed by qualitative descriptive way that describes and explains precisely in accordance with the actual situation about the problems in the carefully derived from data that has been collected so that can be drawn conclusions appropriately. The results showed that 64% of the respondents acknowledged the existence of a very important role of local community leaders, while 36% of the community expressed no role from either government in terms of providing socialization / training on how to manage good waste. While 58% of the respondents stated that the infrastructure facilities for waste management of Village Karang Intan are still lacking, while the remaining 32% assumed that theinfrastructure was enough because the respondent community was in front of the road contained in the trash bin, 10% of the respondents did not there is an answer. Public participation in waste managementdirectly 54% of respondents did not carry out activities directly to manage the environment, and 16% rarely did, and 7% of respondents were quite frequent and 16% frequently carried out waste managementactivities.